Design of Wideband Circular-Slot Antenna for Harvesting RF Energy. (19th July 2022) - Muhammad, Surajo; Smida, Amor; Waly, Mohamed Ibrahim; Mallat, Nazih Khaddaj; Iqbal, Amjad; Reza Khan, Sadeque; Alibakhshikenari, Mohammad
Abstract : The design of a wideband circular-slot antenna for RF signal harvesting is reported in this work. The proposed design frequency range accommodates the leading contributors to the available RF signals accessible by the RFEH node. These widely utilized frequency bands comprise GSM1800, UMTS2100, Wi-Fi2.450, and LTE2600. The antenna geometry comprises circular-ring radiating component filled with two orbital circular and rectangular slots. At the bottom plane, a pair of rectangular and semirectangular-circle slits are integrated. The antenna presented is designed on a double layer of 1.6 mm high FR-4 substrate. The source antenna achieved a simulated and measured impedance bandwidth (BW) of 1.510 and 1.590 GHz, amounting to 68% and 73% fractional BW (FBW), covering -10 dB reflection coefficient (| S 11 |) between 1.640 to 3.150 GHz and 1.550 to 3.140 GHz, in that order. The wideband circular-slot source antenna realized a maximum measured gain of 1.88, 2.13, 2.81, 3.22, and 4.32 dBi for 1.800, 2.100, 2.450, 2.650, and 3.20 GHz, respectively. The proposed design dimension on the printed board is 0 . 61 λ g  × 0 . 70 λ g . The improved antenna gain is obtained from a circular parasitic patch coupled to the defected ground structure (DGS) for better RF energy harvesting in an ambient environment.